MARKETING EXPENDITURES IN THE INDONESIAN CONSTRUCTION INDUSTRY - Krishna Mochtar (Civil Engineering Dimension, 2004)
In the 1960s, a ânewâ marketing concept known as "four Ps marketing mix" appeared and shifted the focus from the product to the customer. The objective of the new concept was not only profit, and the means of achieving the objective expanded to include the entire âmarketing mixâ: product, price, promotion, and place (channels and distribution). Expenditures of marketing in a company should be explored from these mixes, because each mix would have an impact on the total marketing expenditures. These four mixes are the main aspects of marketing and thus, should represent almost all expenditures in marketing in a company. From this research it is discovered that the responding contractors have only average efforts to improve or innovate their service, mostly using the latest construction methods and management approach. Correlated to their policy in the fourth mix (Place), they are still national oriented and not international oriented in marketing their services, this may lead to the big question of their survival; their motivation to innovate is only average while their target market is only national market. Their attitude to use more intensive âfeesâ policy rather than both product innovation and promotion is also interesting. Big percentage of the responding contractors assumes these âfeesâ are regular marketing practices. This attitude may better be stopped to make the construction industry practices healthier. Attitude to use more product innovation and true promotion approach in marketing in construction must be encouraged systematically in the future, to improve competitiveness in the long term.